Views of Aceh Tamiang Ulama Against Postponement of Inheritance Distribution - Lukmanul Hakim (Rechtsnormen: Journal of Law, 2024)
Background. Inheritance should be a pleasant thing for the heirs, but sometimes this becomes a catastrophe that causes a rift or break in the family relationship, this is due to the greed of the heirs, including problems in inheritance is the delay in distribution to the heirs. Purpose. The inheritance is the absolute right of the heirs who should be immediately divided after paying off the debts and assets of the heirs, but because the distribution is not hastened, it has an unfavorable impact on the heirs. Method. The research method used in this research is qualitative research, this type of research is field research whose main source is the results of interviews in the field. Results. The results of this study are: 1) The impact of delaying the division of inheritance, namely: The occurrence of family problems / disconnection between heirs, can result in the loss of the value of the inherited property, and the persecution of some heirs because their rights are not fulfilled. 2) The view of the Aceh Tamiang Ulama regarding the delay in the division of inheritance is divided into three laws, namely: Obligatory delay, permissible delay and haram delay. These three laws are adjusted to the circumstances that occur if the delay in the distribution of inheritance is due to doubts about nasab and / or doubts about the life of the heirs, it must be postponed until there is a determination of nasab and / or heirs from the court. Conclusion. Likewise, delaying the distribution of inheritance due to doubts caused by real pregnancy or doubts about the sex (khunsa) is obligatory until the status of both is clarified. Delaying the distribution of the inheritance, if there is agreement from all the heirs who are entitled to it, and if it is permissible and managed in accordance with shar'i law, is permissible. If delaying the distribution of the inheritance results in injustice to the heirs or results in damage and loss of value to the inheritance, then it is haraam.